Pathology of the Process of Selecting Military Ranks in Arabic Dictionaries - Fatemeh Zarei; Ali Afzali; Shahriar Niazi (پژوهش‌های ترجمه در زبان و ادبیات عربی, 2021)
One of the problems for translators is the adaptation to military ranks. The difficulty of a translator is doubled when the number of military ranks in the source and target languages is not the same; as a result, these terms remain unequal in one of the two languages, because there are differences in the military structure of the armed forces of countries that ignoring them can create problems for translators. After describing Iran's military ranks and comparing it with Arab countries, the present study examines general and specialized dictionaries and investigates how to find their equivalence, using a descriptive-analytical and comparative method. The results indicate that most of the general dictionaries did not have sufficient knowledge of specialized fields and did not study the terms of this field carefully and specialized dictionaries could not be equivalent due to the fact that they were written by military people and had no information about the structure of Arab countries. The best way to choose an equivalent for the terms of military ranks is "equivalent selection after recognizing the pattern of military ranks of Iran and Arab countries.